Audit of babiven maintenance total parenteral nutrition. Issue 4 (11th March 2011) - Walton, R
Abstract : Objective: To determine the appropriateness of Babiven Maintenance TPN in premature babies, to ensure they gain weight at an appropriate rate and maintain their electrolytes, glucose and albumin in appropriate ranges. Methods: Patients were identified using the pharmacy computer programme. Twenty consecutive patients were chosen retrospectively, to prevent bias in the prescribing for babies who were on the neonatal unit at City Hospital. Data such as gestational age, weights, indication for TPN and need for insulin were collected from the neonatal electronic system 'Badger'. Information was collated using a proforma and data was entered into an Excel spreadsheet for analysis. Calcium was corrected to account for albumin. Results: Twenty babies were included in the audit, 10 male and 10 female. The average gestation was 28 weeks and 6 days (25+4–33+0). The average birth weight was 1207 g (555–1970 g). Fourteen babies (70%) gained weight in the range of 10–20 g/kg/day. Five babies did not gain weight and one baby gained more than 20 g/kg/day. The average weight gain for all babies was 11.4 g/kg/day. The average weight gain for the babies that did gain weight was 15.2 g/kg/day. The average duration on Babiven maintenance was 10 days (2–18). One baby required insulin for hyperglycaemia during the first 2 days of receiving Babiven maintenance TPN. One baby was transferred to another hospital, fifteen stopped when they were having enough enteral feed and four required bespoke TPN bags when Babiven maintenance was no longer appropriate. Reasons for changing from Babiven maintenance were; low potassium and the need for a concentrated bag; low albumin and phosphate; low sodium and phosphate; the need for a concentrated bag for a baby with fluid restriction. No babies had raised potassium, phosphate or albumin levels. Conclusion: None of the audit standards were met; however Babiven maintenance seems adequate in some patients. The electrolyte data suggests that there is scope to increase the content of potassium, phosphate and amino acids in the Babiven maintenance bags; however a larger data set would be required to validate this result.